Examining marianismo gender role attitudes, ethnic identity, mental health, and substance use in Mexican American early adolescent girls. Issue 2 (3rd April 2019) - Sanchez, Delida; Vandewater, Elizabeth A.; Hamilton, Emma R.
ABSTRACT: Given the increased trend in substance use patterns among Latina adolescents in recent years, the need for research that identifies gender-specific and culturally relevant protective factors is essential in tailoring interventions. The current study examined the links between marianismo gender role attitudes, ethnic identity, and substance use abstinence among 277 low-income Mexican American early adolescent girls. Mental health was also examined as a potential moderator in these links. Results of linear regression analysis revealed that familismo, virtuous/chaste, and spiritual marianismo gender role attitudes were predictive of stronger ethnic identity; conversely, self-silencing marianismo attitudes were predictive of weaker ethnic identity. Second, results of hierarchical logistic regressions revealed that both virtuous/chaste marianismo gender role attitudes and mental health (low rates of psychological distress) were inversely linked with substance use; furthermore, they had a combined link that was related to even lower rates of substance use among participants. However, ethnic identity did not have a direct or moderating effect on substance use. Findings suggest that the promotion of positive components of marianismo and mental health may have a protective effect against early substance use in Mexican American early adolescent girls.